The Implementation of Make a Match Method Using the Jakarta Post to Improve Students’ Reading Skills - Ratri, Nanda Lintang; Widya Lestari, Maria Yosephin; Nur'aini, Siti (Lingua Franca, 2024)
The main objectives of the study are 1) to find out students reading mastery before being taught by applying Make a Match using The Jakarta Post in the learning process. 2) to find out students reading mastery after being taught by applying Make a Match using The Jakarta Post in the learning process. 3) to find out the differences between the students reading mastery taught by applying by Make a Match and without applying Make a Match using The Jakarta Post in the learning process. In this case, the researcher adopted Quantitative Research. This study took data sources of 72 students from class X Man 1 students in Semarang. Then the researcher made an instrument by making double choice questions as a pre-test and post-test to assess students' reading progress after being taught Make a match as a method and applied to the text in the form of Jakarta post. The result of pre-test mean of both classes is 66.25 for experiment class and 61.39 for control class. And the result of post-test mean of both classes is 85.97 for experimental and 74.03 for control class. Those result were formulated with t-test formula. The test score showed that t-test > t-table. The t-test is obtained 1.935 for 5 percent (0.05) alpha level of significant. The percentage of t-table 5% is -2,021. The computation shows that 1,935 > -2,021. The conclusion of this study is to improve students’ reading by applying Make a Match using The Jakarta Post is recommended and effective.